Pengaruh Aroma Terapi Peppermint Terhadap Mual Muntah Pada Pasien Post-General Anestesi Dengan Operasi Apendiktomi Perforasi: The Effect of Peppermint Aromatherapy on Nausea Vomiting in Post-General Anesthesia Patients with Perforated Appendectomy - Purwaningsih, Lilik; Tresya, Elvie (Indonesian Scholar Journal of Nursing and Midwifery Science, 2023)
Introduction: Postoperative nausea and vomiting are complications that often occur in general anesthesia in the first 24 hours after surgery.  Methods: This study uses a quantitative method using a pre-experimental design type one group pre-test-post-test. The population in this study were post general anesthesia patients with appendectomy surgery with perforation as many as 34 people. The sampling technique used inclusion and exclusion criteria. So, the sample in this study was 15 people. The research instrument used was the PONV Assessment Sheet Checklist. The statistical test used is the T-test.  Results: Based on the results of the study, it is known that the results of the Wilcoxon signed test obtained a Z value of -4,447 and a sig value. (2-tails) 0,000 < 0,05.  Discussion: The conclusion is that there is an effect of peppermint aroma therapy on reducing nausea and vomiting in post-general anesthesia patients with appendectomy with perforation.